Plaque fluoride concentrations associated to the use of conventional and low-fluoride dentifrices - Pessan, Juliano Pelim [UNESP]; Manarelli, Michele Mauricio [UNESP]; Kondo, Karina Yuri [UNESP]; Italiani, Flavia de Moraes; Nakai Kobayashi, Claudia Ayumi; Whitford, Gary Milton; Delbem, Alberto Carlos Botazzo [UNESP]; Rabelo Buzalaf, Marilia Afonso (Mosher & Linder, Inc, 2013)
Purpose: This double-blind, crossover study evaluated whole plaque fluoride concentration (F), as well as whole plaque calcium concentrations (Ca) after brushing with a placebo (PD - fluoride free), low-fluoride (LED, 513 mu g F/g) and conventional (CD, 1,072 mu g F/g) dentifrices. Methods: Children (n=20) were randomly assigned to brush twice daily with one of the dentifrices, during 7 days. On the 7th day, samples were collected at 1 and 12 hours after brushing. F and Ca were analyzed with an ion-selective electrode and with the Arsenazo III method, respectively. Data were analyzed by ANOVA, Tukey's test and by Pearson correlation coefficient (P< 0.05). Results: The use of the fluoridated dentifrices significantly increased plaque [F]s 1 hour after brushing when compared to PD, returning to baseline levels 12 hours after. Positive and significant correlations were found between plaque [F] and (Ca) under most of the conditions evaluated. The mean increase in plaque [F] observed 1 hour after brushing with the CD were only about 47% higher than those obtained for the LFD. The use of a LFD promotes proportionally higher increases in plaque [F] when compared to a CD. Plaque F concentrations were also shown to be dependent on plaque Ca concentrations.